Characterization of the pseudorabies virus-specific immunoglobulin M response and evaluation of its diagnostic use in pigs with preexisting immunity to the virus. - Kimman, T G (1993)
Despite preexisting immunity to pseudorabies virus (PRV), pigs may become infected and may or may not show clinical signs of disease. To investigate whether detection of immunoglobulin M (IgM) antibodies to PRV is suitable for diagnosis of recent infection in pigs with (or without) preexisting immunity, the IgM responses of pigs were examined after both experimental and natural infections. Upon inoculation of seronegative pigs with a low dose of a mildly virulent strain of PRV, IgM was first detectable at day 7 postinoculation (p.i.), reached a maximum at day 14 p.i., and became undetectable again at about days 32 to 36 p.i. In inoculated pigs with maternal antibodies against PRV, the IgM response began later and ended sooner, and peak titers were also lower. In immune pigs with maternally derived antibodies, there was apparently no correlation between the virulence of the inoculated strain and the IgM response. The suitability of the IgM enzyme-linked immunosorbent assay (ELISA) for detection of recent infection in the field was compared with that of the virus neutralization (VN) assay and with an ELISA which specifically detects antibodies directed to glycoprotein I (gI) of PRV. Paired sera were obtained from pigs suspected of PRV infection in an area endemic for PRV infection in which vaccination against PRV is often applied. Practically all pigs had antibodies to PRV in the acute phase of the disease. Compared with the VN assay, the specificity of the IgM ELISA was high but its sensitivity was low. However, all three serotests apparently failed to detect some PRV infections. The IgM ELISA appeared to be especially useful as a diagnostic aid for detection of recent infections in pigs with high levels of neutralizing and gI antibodies, probably maternally derived, in the acute phase of the disease. Such pigs may fail to develop a significant rise in VN antibody titer. The IgM ELISA may be the only serotest for monitoring infections in such pigs.